Mental distress and inflammation in bladder cancer: The nerve makes things less vague - Iveta Mikolaskova; Yori Gidron; Vladimira Durmanova; Magda Suchankova; Maria Bucova; Luba Hunakova (Brain, Behavior, & Immunity - Health)
Objectives: This study aimed to explore the interaction between perceived stress, life satisfaction, heart rate variability (HRV), and immune-inflammatory markers in bladder cancer patients. We investigated how HRV moderates the relationship between psychological distress and levels of TNF-α and TGF-β cytokines. We hypothesized that high vagal nerve activity, as indicated by higher HRV, mitigates the impact of perceived stress and life dissatisfaction on inflammation. Methods: The study included 73 patients with bladder cancer. HRV was determined from a 5-min ECG recording, focusing on the standard deviation of normal-to-normal interbeat intervals (SDNN). Psychological distress was measured using the Perceived Stress Scale (PSS), and life satisfaction was evaluated with the Life Satisfaction Questionnaire (LSQ). Serum concentrations of TNF-α and plasma levels of TGF-β were determined using sandwich ELISA. Results: We found evidence that HRV modulates the relation between perceived stress and inflammation. In patients with low HRV (SDNN <20 ms), PSS was positively correlated with serum level of TNF-α and negatively with the level of TGF-β, while life satisfaction was positively correlated with TGF-β. These relationships were not significant in patients with high HRV (SDNN ≥20 ms). Conclusion: Our findings suggest that high vagal activity, as indicated by higher HRV, may mitigate the adverse effects of psychological distress on immune-inflammatory responses in patients with bladder cancer. Stress-related inflammation took place under conditions of low HRV, highlighting the potential role of autonomic regulation in cancer prognosis. Future research should further explore these relationships to develop interventions aimed at improving patient outcomes through stress management and enhanced vagal nerve activity to regulate inflammation in cancer.